Cholinesterase as an inflammatory marker of subclinical infection of dairy cows infected by Neospora caninum and risk factors for disease - Appelt M.A. (2019)
© 2019 Elsevier LtdThe aim of this study was to evaluate the seroprevalence of Neospora caninum in dairy cows, as well as to verify the risk factors for N. caninum infection and inflammatory response in dairy cows. Using the indirect immunofluorescence reaction, the seroprevalence of neosporosis was determined to be 32.82%. Based on regression analysis, the presence of dogs at a farm increased the probability of a cow testing positive for N. caninum (OR = 20.01 [5.21–123.12]). These data suggest that N. caninum has a relevant prevalence in dairy cows of the Microregion of Rio do Sul (Brazil), with elevated frequencies of anti-N. caninum IgG. The data also suggest that the parasite is widely distributed in dairy herds of the micro-region, because 94.4% of properties screened had at least one seropositive animal. The principal risk factors for disease maintenance in herds may be considered the presence of dogs and absence of a diagnostic test when introducing new animals. Blood from these cows was used to measure variables related to the inflammatory response. Serum cholinesterase activity, as well as serum levels of globulins and C-reactive protein were higher in seropositive to N. caninum than in seronegative cows. Furthermore, the infection by parasite causes an intense inflammatory process, contributing to disease pathophysiology.